Prevalence and factors associated with modern contraceptive use among women of reproductive age in 20 African countries: a large population-based study - Robert Akparibo; Paschal Awingura Apanga; Maxwell Tii Kumbeni; Emmanuel Awine Ayamga; Mark B Ulanja (BMJ Open)
Objective To assess the prevalence and factors associated with modern contraceptive (CP) use among women of the reproductive age.Design Cross-sectional study.Setting We used data from the Multiple Indicator Cluster Surveys (MICSs) from 20 African countries collected between 2013 and 2018.Participants Data on 1 177 459 women aged 15–49 years old.Methods Multivariable logistic regression was used to identify factors associated with modern CP use, while controlling simultaneously for independent variables, and accounting for clustering, stratification and sample weights from the complex sampling design. We used random effects meta-analysis to pool adjusted estimates across the 20 countries.Results The overall prevalence of modern CP use was 26% and ranged from 6% in Guinea to 62% in Zimbabwe. Overall, injectable (32%) was the most preferred method of CP, followed by oral pill (27%) and implants (16%). Women were more likely to use a modern CP if they: had a primary (adjusted prevalence odds ratios (aPORs): 1.68, 95% CI: 1.47 to 1.91)) or secondary/higher education (aPOR: 2.16, 95% CI: 1.80 to 2.59) compared with women with no formal education; had no delivery in the last 2 years (aPOR: 3.89, 95% CI: 2.76 to 5.47) compared with women who delivered in the last 2 years; were aged 25–34 years (aPOR: 1.33, 95% CI: 1.20 to 1.47) compared with women aged 15–24 years; were of middle-income status (aPOR: 1.25, 95% CI: 1.11 to 1.39) or rich (aPOR: 1.53, 95% CI: 1.27 to 1.84) compared with poor women and had two or more antenatal care visits compared with women without a visit. Perceived domestic violence was not associated with modern CP use (aPOR: 0.98, 95% CI: 0.92 to 1.05).Conclusion Our findings are relevant in a global context, particularly in the African region, and improve our understanding on relevant factors essential to increasing modern CP use.